Implementation of Interactive Mathematics Teaching E-Modul To Improve Student Motivation and Learning Outcomes - Adi Candra Kusuma; Silvia Rahmi Ekasari; Eva Weddakarti (Hipotenusa : Journal of Mathematical Society, 2022)
Online learning requires lecturers to have creativity in choosing the right learning method to be able to create fun learning facilities. Mathematics synonymous with difficult courses needs an interactive learning approach. The purpose of this research is to Effectiveness produce interactive mathematics teaching materials to improve student motivation and learning outcomes. This type of quantitative research is carried out on students of class 1A as an experimental class and 1B as an even semester control class for the academic year 2021/2022. Data collection methods use questionnaires, observations, and test questions by processing normality test data, homogeneity test, completion test, bending test, and regression test. The results showed that individual learning completion surpassed KKM (68), and student learning outcomes with Interactive Mathematics teaching materials were higher than using expository learning. There is support for the influence of motivation on student learning outcomes by 78.6% with regression equation Y = 59.064 + 1.421 X, the with positive motivation of experimental class by 83% compared to control class 69%. The math learning that students expect is more fun and less boring.